Antifungal Activity of Essential Oils of Leaves, Rhizomes Oils and Fraction Wild Ginger Elettariopsis Slahmong Ck Lim Inhibit The Colony Growth of Sclerotium Rolfsii - Nurmansyah Nurmansyah; Herwita Idris; Nasril Nasir (Journal of Applied Agricultural Science and Technology, 2021)
This study aims to see the effectiveness  of essential oils of leaves, rhizomes and fraction of wild ginger Ellettariopsis slahmong CK Lim against the pathogenic fungus Sclerotium rolfsii which causes rot disease of the stem base of peanut plants an in vitro.The study consisted of two sub activities: (a) inhibited of colony diameter using Patato Dextrosa Agar (PDA) medium and (b) inhibited of colony biomass using Potato dextrose Broth (PDB) medium, the treatments tested were leaf essential oil and rhizome of wild ginger and fractions A1, B2, C3 and D4, with concentration levels (0, 100, 250 and 500 ppm). Experiments (a) and (b) were arranged in the form of a Completely Randomized Design (CRD) in factorial each with 4 replications. The results showed that the leaf essential oil and rhizome of wild ginger and its fractions had the potential to be used as a vegetable fungicide. The A1 fraction has the best antifungal effectiveness compared to the B2 fraction, leaf oil, rhizomes and other fractions, with the highest inhibition of diameter and biomass of S rolfsii colony the 49.47% and 51.46%. Essential oils of leaves and rhizome oil are not statistically significantly different, but in numerically leaf oil are better than rhizome oil. The C3 fraction showed the lowest colony diameter inhibition and biomass of 34.70% and 36.95%. The best concentration level in inhibition the growth of S rolfsii mushroom is 500 ppm, with inhibition of the diameter and biomass of the colony by 81.74% and 84.25%.